Comparison of Electroencephalography in Patients With Seizures Caused by Neurosyphilis and Viral Encephalitis - Zheng, Li-Li; Chen, Jing-Zhen; Zhuang, Xiao-Rong; Miao, Jia-Yin (Frontiers in Neurology, 2022)
Background: Neurosyphilis (NS) lacks specificity in clinical and imaging features, and patients are frequently misdiagnosed as viral encephalitis when they present with seizures. This study aimed to compare electroencephalography (EEG) in patients with seizures resulting from the two diseases and provide guidance for differential diagnosis. Methods: A retrospective study on patients diagnosed with neurosyphilis and viral encephalitis with seizures in the Department of Neurology, Zhongshan Hospital, Xiamen University from 2012 to 2020. Results: A total of 39 patients with seizures caused by neurosyphilis and 40 patients with seizures caused by viral encephalitis were included. Chi-square test analysis showed that compared with patients with viral encephalitis, patients with neurosyphilis mainly developed in middle-aged and elderly people (p < 0.001), were more likely to have temporal epileptiform discharges (p < 0.001), and less likely to have status epilepticus (SE) (p = 0.029). There was difference between two groups in the EEG performance of lateralized periodic discharges (LPDs) (p = 0.085). The two groups were matched for age and sex by case-control matching, and 25 cases in each group were successfully matched. Patients with neurosyphilis were more likely to have temporal epileptiform discharges than those with viral encephalitis (p=0.002), and there were no significant differences in LPDs (p=0.077) and SE (p=0.088) between two groups. Conclusion: When EEG shows temporal epileptiform discharges, especially in the form of LPDs, we should consider the possibility of neurosyphilis.